Three new eriophyoid mite species in the tribe Phyllocoptini from Yunnan Province, southwestern China (Acari: Eriophyidae: Phyllocoptinae) - Han, Xiao; Xue, Xiao-Feng; Hong, Xiao-Yue (Zootaxa, 2013)
In this paper, three new Phyllocoptini eriophyoid mite species from Yunnan Province, China are described and illustrated: Proiectus rodgeseta sp. nov. on Pinus armandii Franch. (Pinaceae), Proiectus granularpro sp. nov. on Pinus tabuliformis Carr. (Pinaceae) and Phyllocoptruta juniperiana sp. nov. on Juniperus chinensis Linn. (Cupressaceae). All are vagrants causing no apparent damage to their host plants. A key to the species of Proiectus is provided.